Odpowiedź :
Odpowiedź:
a) -3x+x=-8
-2x=-8
x=2
b) 4x=36/:4
x=9
c)2 (x+3)=10
2x+6=10
2x=4/:2
x=2
d) 5-2(x+2)=9
5-2x-4=9
-2x=9-1
-2x=8/:2
x=-4
e)6(x+4)=5x+1+x
6x+24=6x+1
6x-6x= -24+1
0=-23??
f) [tex]\frac{1}{4}[/tex]y+[tex]\frac{3}{4}[/tex]=[tex]\frac{7}{4}[/tex]
[tex]\frac{1}{4}[/tex]y=[tex]\frac{7}{4}[/tex]-[tex]\frac{3}{4}[/tex]
[tex]\frac{1}{4}[/tex]y=[tex]\frac{4}{4}[/tex]/:[tex]\frac{1}{4}[/tex]
y=4
Szczegółowe wyjaśnienie:
a)-3x+x=-8
-2x=-8
x=4
b)4x=36
x=9
c)2(x+3)=10
x+3=5
x=5-3
x=2
d)5-2(x+2)=9
5-2x-4=9
1-2x=9
-2x=9-1
-2x=8
x=-4
e)6(x+4)=5x+1+x
6x+24=6x+1
24=1
wyrażenie nie prawdziwe
f)1/4y+3/4=7/8
y+3=7
y=7-3
y=4
-2x=-8
x=4
b)4x=36
x=9
c)2(x+3)=10
x+3=5
x=5-3
x=2
d)5-2(x+2)=9
5-2x-4=9
1-2x=9
-2x=9-1
-2x=8
x=-4
e)6(x+4)=5x+1+x
6x+24=6x+1
24=1
wyrażenie nie prawdziwe
f)1/4y+3/4=7/8
y+3=7
y=7-3
y=4